Pengaruh Karakteristik Perusahaan terhadap Tax Avoidance pada Perusahaan BUMN Sektor Transportasi 2018 - 2022 - Muhammad Abdul Rahman; Maulana Iskak (Syntax Corporation Indonesia, 2025)
This research aims to analyze the influence of company characteristics which are proxied through the variables leverage, size, profitability and capital intensity on the tax avoidance variable in state-owned companies in the transportation industry. In this study, the data used by the researcher to carry out in-depth analysis and testing was obtained through secondary data collected by the researcher from the financial reports of state-owned companies in the transportation industry in the period 2018 to 2022. The sample used by the researcher used the purposive sampling method which has been used. determined and collected as many as 44 companies whose criteria had been determined by researchers. The results of this research show that the leverage, size and capital intensity variables have no influence on tax avoidance, while the ROA and ROE variables have a significant influence on tax avoidance. The novelty offered in this research is that researchers tested tax avoidance practices through several variables that have been determined in the transportation sector in government-owned companies, in this case BUMN, which is one type of industry that often escapes public scrutiny, so this is quite interesting to research.